Pembuatan Indeks Beranotasi Jurnal Ilmiah Bidang Humaniora di Perpustakaan Kopertis Wilayah X - Purba, Iin Fridayani Veronika; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study to describe process production index anotation of journal humaniora at Libraries Kopertis Region X. Method that use is deskriptif method, it’s meaning describe the real data. The data get from observation to library and study of library. Match with analysis process production index anotation is: (1) select the indexing procedure that: doing control and selection, choose the part that will describe, choose the key word and make anotation, with select the rule of describe; (2) certainty that use in indexing is: the part of journal, certainty the name of author, title of article, element that will use, and formation of index; (3) and the last process is write the index anotation.